1999
DOI: 10.1074/jbc.274.9.5692
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Induces Expression of Uncoupling Protein-2 in Hepatocytes and Promotes Liver ATP Depletion

Abstract: Uncoupling protein 2 (UCP2) uncouples respiration from oxidative phosphorylation and may contribute to obesity through effects on energy metabolism. Because basal metabolic rate is decreased in obesity, UCP2 expression is predicted to be reduced. Paradoxically, hepatic expression of UCP2 mRNA is increased in genetically obese (ob/ob) mice. In situ hybridization and immunohistochemical analysis of ob/ob livers demonstrate that UCP2 mRNA and protein expression are increased in hepatocytes, which do not express U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

36
313
1
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 405 publications
(360 citation statements)
references
References 48 publications
36
313
1
5
Order By: Relevance
“…As mentioned above, up-regulation of UCPs as an adaptive response to obesity results in hepatocyte ATP depletion when energy needs are acutely increased. Importantly, these studies demonstrated that hepatic necrosis occurred only when mitochondrial electron transport was inhibited [51,54]. Similarly, Diehl and colleagues demonstrated using 31 P NMR spectroscopy that recovery from hepatic ATP depletion is severely impaired in NASH patients [56] suggesting a NASH dependent bioenergetic defect.…”
Section: Mitochondria Dysfunction In Fatty Liver Diseases -Bioenergetmentioning
confidence: 93%
See 4 more Smart Citations
“…As mentioned above, up-regulation of UCPs as an adaptive response to obesity results in hepatocyte ATP depletion when energy needs are acutely increased. Importantly, these studies demonstrated that hepatic necrosis occurred only when mitochondrial electron transport was inhibited [51,54]. Similarly, Diehl and colleagues demonstrated using 31 P NMR spectroscopy that recovery from hepatic ATP depletion is severely impaired in NASH patients [56] suggesting a NASH dependent bioenergetic defect.…”
Section: Mitochondria Dysfunction In Fatty Liver Diseases -Bioenergetmentioning
confidence: 93%
“…NAFLD). Early studies by Diehl and colleagues reported that obesity induced steatosis was associated with increased expression of uncoupling protein-2 (UCP-2) in liver, which promoted ATP depletion [51]. This results from increased H + leak across the inner mitochondrial membrane, which dissipates the membrane potential and decreases ATP synthesis.…”
Section: Mitochondria Dysfunction In Fatty Liver Diseases -Bioenergetmentioning
confidence: 99%
See 3 more Smart Citations